Expression of Greetings by Indonesian EFL Learner - bukhori bukhori (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This study investigates the strategies of Indonesia EFL learners employed for expressing greeting in different status and gender. 25 students from English Education Department of State Islamic University of Sultan Syarif Kasim Riau asked to fulfill Discourse Completion Test (DCT). The result indicated that there are variation of strategies in performing greeting in relation to contextual variable which include gender (male and female) and status (high and equal) of interlocutor. The findings suggested that gender did not influence EFL learners’ initiating act of greeting expression. Meanwhile, status of interlocutor influenced EFL learners’ greeting expression. Finally, expression “assalamu’alaikum” used by almost all EFL learners to both higher status interlocutors (male and female) who have good understanding of Islamic doctrines. And female EFL learners tend to use non verbal form of greeting rather than male EFL learners.